Utilização de aprendizagem de máquina para classificação de e-mails em categorias relevantes - Silva, Bruno Ferreira (Universidade Federal de São Carlos, 2021)
One of the main technology tools currently used to exchange information is the email service. However, managing the high volume of information received is one of the major challenges encountered in using this service in public and private institutions. Automated text classification has been considered an essential method to handle a high of textual information that people have to deal with on a daily basis. Problem solving by electronic and automatic means is increasingly common due to the reduction of manual work and costs. With that in mind, companies that receive support requests via email have been trying to reduce service time by using machine learning algorithms to sort texts sent via email. This study aims to identify the ability of machine learning algorithms to correctly determine categories, using a previously labeled database. The results were calculated as means and standard deviations of the most used metrics in machine learning, as well as the execution time of the four algorithms used. The results showed themselves to be satisfactory and well functional.
Machine Learning algorithms for email subject classification
Keywords: aprendizado de máquina; reconhecimento de padrões; bag of words; classificação supervisionada; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO